Feasibility of Marine Microalgae Immobilization in Alginate Bead for Marine Water Treatment: Bead Stability, Cell Growth, and Ammonia Removal - Chen-Lin Soo; Cheng-Ann Chen; Othman Bojo; Yii-Siang Hii (International Journal of Polymer Science)
Sodium alginate is the most commonly used polymer matrix in microalgae immobilization for water treatment. However, the susceptibility of alginate matrixes to cation chelating agents and antigelling cation limits the use of alginates in estuarine and marine systems. Hence, the present study aims to investigate the stability of alginate bead in marine water and the feasibility of microalgae to grow when immobilized in alginate bead for marine water treatment. Different concentrations of alginate and hardening cation calcium were used to formulate beads. The beads were incubated in Guillard’s f/2 medium and shaken vigorously by using orbital shaker for 15 days. The results indicated that bead stability was enhanced by increasing alginate and CaCl2 concentrations. Subsequently, the marine microalga, Nannochloropsis sp., was immobilized in calcium alginate bead. The growth and ammoniacal-nitrogen (NH4+-N) uptake by immobilized cell were compared with free cell culture in f/2 medium. Specific growth rate of immobilized cell (0.063 hr−1) was significantly higher than free cell (0.027 hr−1). There was no significant difference on specific uptake rate of free cell and immobilized cell; but immobilized cell removed significantly more NH4+-N (82.2%) than free cell (47.3%) culture at the end of the experiment. The present study demonstrated the potential use of alginate immobilization technique in marine microalgae culture and water treatment simultaneously.